Design and development of an android-based “Flash Card Geometry” application: Exploring students' responses - Hidayati, Yulia Maftuhah; Arifin, Achmad Januar; Setiadi, Arief; Kusuma, Anton Adi Suryo; Kholid, Muhammad Noor (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: Geometry is an essential component of elementary mathematics that helps students develop spatial understanding and abstract thinking skills. However, many students face difficulties in learning geometry due to the abstract nature of its concepts. This study aims to explore the responses of primary school students in the learning process.Method: This study adopted a qualitative approach with a descriptive design. This research involved 15 grade V students at SD Negeri 008 Sangkulirang as participants. Data collection in this study was carried out through the questionnaire method. Data collected through questionnaires were analyzed using a descriptive approach.Findings: The research findings indicate an increase in the average percentage in the aspects of learning, appearance, and technical quality and effectiveness of the program, with all aspects reaching above 80% after the revision. The first revision, the addition of a learning video, provides significant visual support in clarifying concept understanding, while the second revision, the addition of a timer feature in the quiz section, serves to train students' ability to manage time effectively.Significance: The development of this media highlights the innovative integration of digital technology to enhance mathematics learning. Flash Card Geometry is tailored to students’ needs in the digital era, encouraging active participation. Practically, it offers teachers an effective learning tool; theoretically, it supports the use of digital media to promote student-centered learning.